Assessment of green building codes relating to building facades for mitigating urban heat island in Malaysia - Aldoumani, Nouralden (Kulliyyah of Architecture and Environmental Building, International islamic University Malaysia, 2020)
Urban Heat Island (UHI) is a major issue in the developed and developing countries. It is one of the consequences of urbanization and a known reason behind the global warming. In fact, such a rapid growth brought about adverse environmental effects including the UHI effect. To mitigate the adverse caused by the rapid development, the nation initiated the Malaysian Standard (MS)1525 and the Green Building Index (GBI). The present study opined that the energy rating tools focused much more on the performances inside the buildings in increasing energy efficiency and affording the comfortability for building occupants. However, such tools have not paid too much attention to the effects on the outside environment of the buildings. In this respect, Biomimicry has emerged as a new science which has been introduced recently for studying the nature's ideas and applying them to our buildings for the purpose of improving the quality of those buildings. Therefore, this study attempts to investigate the performance of the facades that advocated sustainable design principles either by subscribing to GBI directly or to the Biomimicry Life's Principles (BLP) indirectly, focusing on the criteria of the GBI and BLP applications for the facades of commercial buildings. Content Analysis and temperature monitoring are the main methodologies for this study. The analysis of data of the present study revealed that the representation of facades was 16% and 75% in GBI and BLP, while the presentation of UHI was 6% and 35% in GBI and BLP, respectively. Applying this against the two case buildings, the representation of the criteria of facades was 38% and 50% presences. This finding was in line with the energy rating for the buildings, where Silver achieved a lesser percentage and Gold achieved the more percentage. The findings of data monitoring also concurred where the building with the lesser percentage of façade representation was recoded to have a higher ground surface temperature than the others. Moreover, the results of the study expounded on good grounds which help mitigate UHI, and the facades of buildings need to be efficient and follow sustainable guidelines with Biomimicry enhancements. The study provided useful suggestions as well as recommendations for architects in terms of the design which is highly suitable for commercial facades which minimize the effect of temperature of UHI in Malaysia.